1983
DOI: 10.1007/bf00041830
|View full text |Cite
|
Sign up to set email alerts
|

Elevated atmospheric partial pressure of carbon dioxide and dry matter production of konjak (Amorphophallus konjac K. Koch)

Abstract: Konjak (Amorphophallus konjac K. Koch) was grown under normal (350 μbar) or enriched (700 μbar) CO2 partial pressure in glasshouses kept at 33/26 °C. Doubling the CO2 partial pressure resulted in twice the yield of corm because the net CO2 assimilation rate doubled and, due to the simple source-sink relationship, the increased production was partitioned to the corm. The response to CO2 of assimilation by konjak is discussed in relation to its original habitat in the tropics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Oberbauer et al (1985) reported similar results from their study of tropical pioneer and climax tree species. Many other workers have observed increased biomass production in various species, including a variety of tropical species (Downton et al 1990;Ziska et al in press), temperate trees Norby et al 1986;Hollinger 1987;Arnone and Gordon 1990), agricultural crop species (Wong 1979;Imai & Coleman 1983;Rogers 1983;Del Castillo et al 1989), a vine (Sasek & Strain 1989) and a succulent CAM species (Idso et al 1986;Szarek et al 1987). In contrast to these observations of marked growth enhancement due to elevated CO2, Tolley & Strain (1984a) reported no significant enhancement in growth of P. taeda seedlings.…”
Section: Total Biomass Productionmentioning
confidence: 62%
“…Oberbauer et al (1985) reported similar results from their study of tropical pioneer and climax tree species. Many other workers have observed increased biomass production in various species, including a variety of tropical species (Downton et al 1990;Ziska et al in press), temperate trees Norby et al 1986;Hollinger 1987;Arnone and Gordon 1990), agricultural crop species (Wong 1979;Imai & Coleman 1983;Rogers 1983;Del Castillo et al 1989), a vine (Sasek & Strain 1989) and a succulent CAM species (Idso et al 1986;Szarek et al 1987). In contrast to these observations of marked growth enhancement due to elevated CO2, Tolley & Strain (1984a) reported no significant enhancement in growth of P. taeda seedlings.…”
Section: Total Biomass Productionmentioning
confidence: 62%
“…As the CO 2 concentration is higher in tropical rain forests, up to 510~l l~I at ground level (Aoki, Yabuki, and Koyama, 1975) or even more (1,000~ll-l; Blanc, 1989), this peculiar Ci response may be related to a physiological adaptation of photosynthesis to high CO 2 concentrations. Indeed, for some species at least, it has been demonstrated that at high Ci, plants grown at elevated CO 2 concentration have higher CO 2 assimilation rates than plants grown at normal CO 2 concentration (see Imai and Coleman, 1983;Von Caemmerer and Farquhar, 1984). This can also be related to an unusually high ratio of RuBP-regeneration capacity to Rubisco activity (Walters and Field, 1987).…”
Section: Results-photosynthetic Gas Exchange Characteristics-mentioning
confidence: 99%